1998
DOI: 10.1046/j.1365-3040.1998.00310.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exposure to humid air on epidermal viability and suberin deposition in maize (Zea mays L.) roots

Abstract: When the basal zones of 4-d-old hydroponically grown maize (Zea mays L. cv. Seneca Horizon) roots were exposed to moist air for 2 d, the development of both endodermis and exodermis was affected. In the endodermis, Casparian bands enlarged and more cells developed suberin lamellae. The most striking effect was seen in the exodermis. In submerged controls, only 4% of the cells had Casparian bands, whereas in root regions exposed to air, 93% developed these structures. Similarly, in submerged roots 11% of the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 29 publications
3
48
1
Order By: Relevance
“…Hence, aquaporins appeared to contribute substantially to changes in L P with soil water availability. Soil drying caused L P for the mid-root region to decrease by 73%, a greater decrease than for the distal region, perhaps due to the increased suberization and lignification of the periderm during drying (North and Nobel, 1992;Enstone and Peterson, 1998). Under dry conditions, HgCl 2 had no effect on L P or L R, S for the mid-root region, as for the distal region.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Hence, aquaporins appeared to contribute substantially to changes in L P with soil water availability. Soil drying caused L P for the mid-root region to decrease by 73%, a greater decrease than for the distal region, perhaps due to the increased suberization and lignification of the periderm during drying (North and Nobel, 1992;Enstone and Peterson, 1998). Under dry conditions, HgCl 2 had no effect on L P or L R, S for the mid-root region, as for the distal region.…”
Section: Discussionmentioning
confidence: 98%
“…In many species, root L P considerably decreases as the soil dries (Cruz et al, 1992;North and Nobel, 1996;Lo Gullo et al, 1998). Such decreases are associated with substantial anatomical modifications, such as the development of Casparian bands and suberin lamellae in the exodermis and the endodermis (Enstone and Peterson, 1998;North and Nobel, 2000). The roots of most dicotyledons exhibit secondary growth and produce a suberized periderm outside the stele, which also restricts water uptake (North and Nobel, 1996).…”
mentioning
confidence: 99%
“…We have observed similar anatomy previously in roots of grapevine (Song et al 2011b, Tuladhar andNii 2013), red bayberry (Song et al 2011a) and feijoa (Nii et al 2012) etc. It was concluded by Enstone and Peterson (1998) that endodermal Casparian strip was essential for root function whereas exodermal Casparian strips and suberin lamellae were only an adaptive feature. Enstone et al (2003) have used the term 'physiological sheath' for exodermis and endodermis that play an important role in root function.…”
Section: Discussionmentioning
confidence: 99%
“…The exodermis forms a barrier between the root and the external environment, controlling water and solute influx, and thus is potentially critical for tolerance to water stress (Cruz et al, 1992;Hose et al, 2001). It has been found that there is more rapid suberisation of the exodermal layer in maize roots grown in moist air (aeroponics), vermiculite or stagnant conditions compared to aerated hydroponics (Enstone & Peterson, 1998;Zimmerman & Steudle, 1998). Moreover, in barley, nodal roots are more extensively suberised than seminal roots (Lehmann et al, 2000), and thus hydroponically grown barley roots will have limited suberised exodermal layers compared to equivalent soil-grown plants.…”
Section: Scaling Up: From Hydroponics To the Fieldmentioning
confidence: 99%